Effect of tamsulosin on testis histopathology and serum hormones in adult rats: Experimental study - Yegane Kohestani; Bentolhoda Kohestani; Zahra Shirmohamadi; Masoumeh Faghani (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Tamsulosin is an inhibitory factor of alpha-adrenergic receptors that is used for relieving of the clinical symptoms and management of acute urinary retention. Objective: The aim of this study was to evaluate the effects of tamsulosin on the endocrine axis and testicular tissue in adult male rats. Materials and Methods: In this experimental study, 30 adult male Wistar rats (weighing 250-300 gr) were divided into three groups: 1) control (received distilled water), 2) experimental 1 (received 0.2 mg/kg/day tamsulosin) and 3) experimental 2 (received 0.4 mg/kg/day tamsulosin) through oral gavage for 28 days. Serum hormones level and testicular histopathology were evaluated at the end of the experiment. Results: In this study, the testicular weight decreased significantly in the experimental groups compared to the control group. A significant decrease was seen in testicular weight (p = 0.004) and the number of Leydig cells in tamsulosin-treated groups (p = 0.012). Tamsulosin improved the hormone profile in experimental groups. Also, higher dose of tamsulosin significantly changed the number of Leydig, spermatogonia cells, the thickness of germinal layer, and the diameter of the seminiferous tubules. Conclusion: Results showed that using tamsulosin, possibly reduces the testosterone concentration through adrenergic axis system and in turn has destructive effects on proliferative activity of germ cells.